Factors influence abroad or home post graduates training among medical students: experience from Sudan - Gismalla, Mohamed; Abdallah, Ahmed; Mohammed, Mohammed Alnoor; Mahjoub Taha, Sami (International Journal of Medicine, 2017)
Backgrounds: Commonly, doctors migrate for postgraduate study in African and Middle-east countries to western countries. In this study, we would like to know the percentage of graduates who intended to study abroad and determine the factors of their traveling.Material and methods: This is cross-sectional questionnaire survey. Medical students were asked about their future specialty preference, reasons, and site of training. Also, some demographic data were collected. The data was analyzed by SPSS. P value of < 0.05 was considered significant. Result and Discussion: 197 students responded to our survey and filled the questionnaire properly. Participants knew about future specialty from the teacher, the internet, senior college and advice from a family member with rate 83 (42.1%), 42 (22.8%), 41 (21.3%), and 27(13.7%) respectively. One hundred five (53.3%) of the responders preferred to get their specialty training outside Sudan while the remainder 92(46.7%) preferred local training.The commonest specialty selected among both group are medicine and surgery respectively. Obstetrics and gynecology are selected mainly among students who prefer local training 14 out of 15 totally, with statistically significant (p-value = 0.0001). Residency has significant related to the site of training with (P value 0.03). International recognition and advanced facilities are the commonest cause of traveling abroad among the students. While free hands on training and social reasons are the most common causes of home postgraduates training.Conclusion: More than fifty percent of the participant prefers abroad post-graduates training. The factors which influents site training can be defined as "Pull and Push" factors.